A Pragmatic Study of Speech Acts in the Novel Harry Potter and the Deathly Hallows - I Gede Nika Wirawan; I Made Juliarta (CV. AFDIFAL MAJU BERKAH, 2026)
This study investigates the types and functions of speech acts used by characters in the novel Harry Potter and the Deathly Hallows by J.K. Rowling. Using Searle’s classification of speech act assertives, directives, commissives, expressives, and declarations the research identifies how these linguistic forms contribute to character development, plot progression, and interpersonal dynamics within the story. Through qualitative descriptive methods, selected dialogues are analyzed to determine the intentions behind utterances and the effects they produce on other characters. The findings reveal that assertive and directive speech acts dominate the narrative, reflecting the novel’s themes of conflict, persuasion, and cooperation. Moreover, expressive and commissive acts highlight emotional depth and commitment among characters, while declarations appear less frequently due to the fantasy setting's context of authority and magical institutions. Overall, this study demonstrates that speech acts play a crucial role in shaping narrative meaning and enhancing readers’ understanding of character motivations and relationships in the final installment of the Harry Potter series